Thinking critically about affect in organization studies: Why it matters - Fotaki, Marianna; Kenny, Kate; Vachhani, Sheena J. (Organization (London, England), 2017)
Affect holds the promise of destabilizing and unsettling us, as organizational subjects, into new states of being. It can shed light on many aspects of work and organization, with implications both within and beyond organization studies. Affect theory holds the potential to generate exciting new insights for the study of organizations, theoretically, methodologically and politically. This Special Issue seeks to explore these potential trajectories. We are pleased to present five contributions that develop such ideas, drawing on a wide variety of approaches, and invoking new perspectives on the organizations we study and inhabit. As this Special Issue demonstrates, the world of work offers an exciting landscape for studying the ‘pulsing refrains of affect’ that accompany our lived experiences.